What Factors Affect Conservatism? The Role of Board Gender, CEO Retirement and Financial Distress - Agus Triyani; Sri Retnoningsih; Suhita Whini Setyahuni; Muhammad Fajar Khoiruddin (Universitas Pendidikan Ganesha, 2023)
This research aims to comprehensively analyze the intricate relationships between board gender, CEO retirement, financial distress, and accounting conservatism within the energy sector. Leveraging 164 firm-year observations spanning 2019-2021, our sample selection relied on a purposive sampling technique, with data availability serving as a primary criterion. Through multiple regression analysis, we rigorously tested hypotheses to unveil the nuanced dynamics at play. Contrary to expectations, our findings suggest that board gender does not exert a significant impact on accounting conservatism within energy firms. However, CEO retirement emerges as a pivotal factor positively influencing accounting conservatism. This illuminates the importance of leadership transitions in shaping conservative financial reporting practices. Notably, financial distress demonstrates a contrary effect, negatively impacting accounting conservatism. This novel perspective positions financial distress as a determinant factor, expanding the traditional boundaries of conservatism research within the agency theory framework. Our research significantly contributes to the literature by providing fresh insights into the contextual factors influencing accounting conservatism in the energy sector. The nuanced interplay of CEO retirement and financial distress unveils complex decision-making processes, offering practical implications for corporate governance and financial reporting practices in this industry. This study serves as a valuable resource for both practitioners and scholars seeking a deeper understanding of conservatism determinants in the specific context of energy companies.